The Visible and Less Visible in the Suffering of a Conversion Disorder in Children and Adolescents. A Qualitative Study of Illness Explanatory Models Presented to Caregivers of Children and Adolescents with Conversion Disorder (2018)
Background: Conversion disorder is a challenge for clinicians due to the conceptual gaps as regards its pathogenesis, the way in which it converges with other psychiatric disorders, and the lack of approaches to the experiences of both patients and family members with the disease. Objective: To describe Explanatory Models (EM) offered to caregivers of paediatric patients with conversion disorder who attended the Hospital de la Misericordia. Methods: A qualitative study was conducted with a convenience sample of 10 patients who attended the Hospital de La Misericordia, ¿Bogota? between May 2014 and April 2015. The tool used was an in-depth interview applied to parents and/or caregivers. Results: Caregivers have different beliefs about the origin of the symptoms, especially considering sickness, magical-mystical factors, and psychosocial factors. The symptoms are explained in each case in various ways and there is no direct relationship between these beliefs, the pattern of symptoms, and help-seeking behaviours. Symptomatic presentation is polymorphous and mainly interferes in the patient's school activities. The medical care is perceived as relevant, and psychiatric care as insufficient. Among the therapeutic routes, consultations with various agents are described, including medical care, alternative medicine, and magical-religious approaches. Conclusions: EMs in conversion disorder are varied, but often include magical-religious elements and psychosocial factors. The underlying beliefs are not directly related to help-seeking behaviours or other variables. © 2017 Asociación Colombiana de Psiquiatría